How will individual streaming platforms disrupt the entertainment and retail industries? Insights from Mukbang phenomenon - Ho-Chang Chae (Digital Transformation and Society)
Purpose – Mukbang is a live-streaming format where hosts, often referred to as broadcast jockeys (BJs) or streamers, eat copious amounts of food while engaging with their audience through commentary and reactions. This unique cultural phenomenon has sparked curiosity and diverse reactions globally. Mukbang’s popularity highlights the transformative power of digital platforms on traditional media and society, facilitating a shift toward more interactive and participatory forms of media consumption. This conceptual paper explores Mukbang’s widespread allure through frameworks such as the long tail theory, which illuminates the success of niche markets; parasocial relationship theory, which sheds light on viewers' bonds with streamers and social identity theory, which explains audience loyalty. We also forecast the implications of these streaming trends on the television, retail and sports industries, predicting a broad impact on traditional consumption and engagement models. Design/methodology/approach – This study employs various theories, including the long tail concept, parasocial interactions and social identity theory, to describe and analyze the perplexing yet significant phenomenon of Mukbang. Findings – Digital technology has transformed business models across various media industries, similar to how iTunes and the MP3 format revolutionized traditional music labels. This study suggests that streaming platforms, with their ability to cater to diverse needs and facilitate two-way communication, have the potential to disrupt traditional entertainment and retail industries. Originality/value – This study addresses the gap in understanding how and why streaming platforms like AfreecaTV, Twitch and Huya can disrupt the traditional TV and entertainment industries. It highlights key elements that enable users to become prosumers, broadcasting content such as Mukbang. These platforms outperform traditional entertainment with numerous channels, ease of access, live chat sessions and digital rewards. The ability to build intimate relationships with viewers through two-way communication strengthens parasocial relationships, fostering emotional connections with streamers. Additionally, live chats with other viewers create a sense of belonging and social identity, helping viewers reduce uncertainty and enhance self-esteem.